Effect of the Combining Corn Steep Liquor and Urea Pre-treatment on Biodegradation and Hydrolysis of Rice Straw - Ma, Yulin; Chen, Xu; Khan, Muhammad Zahoor; Xiao, Jianxin; Alugongo, Gibson Maswayi; Liu, Shuai; Wang, Jingjun; Cao, Zhijun (Frontiers in Microbiology, 2022)
A novel pre-treatment using corn steep liquor (CSL) and urea was developed to enhance the enzymatic saccharification and degradability of rice straw (RS). We used RS (1) without (Con) or with additives of (2) 5% urea (U), (3) 9% CSL and 2.5% urea (CU), and (4) 9% CSL and 5% urea (C5U). The result showed that the water-soluble carbohydrate (WSC) conversion of RS reached 69.32% after C5U pre-treatment. Scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, and X-ray diffraction analysis (XRD) confirmed that the surface of pre-treated RS exposed more cellulose and hemicellulose due to the disruption of the resistant structure of lignocellulose. Pre-treated RS significantly decreased neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents and increased crude protein (CP) content, microbial colonization, and induction of Carnobacterium and Staphylococcus attachment. Altogether, we concluded that pre-treatment of a combination of CSL and urea has the potential to improve the nutritive value of RS.